Learning-centred leadership and student achievement: Understanding the mediating effect of the teacher professional community and parental involvement - Özdemir, Nedim; Gun, Feyza; Yirmibeş, Ahmet; Yirmibeş, Ahmet (Sage Publications Ltd, 2021)
This paper examines the links between learning-centred leadership and student achievement through the mediating effect of teacher professional community and parental involvement. Using teacher and student survey data collected from 79 lower secondary Turkish schools in 12 provinces across the country in 2019, this study employs multilevel structural equation modelling. The findings of the current study add to the growing knowledge base in the non-western societies, revealing the impact of principals' leadership on school processes and outcomes in Turkey. The study suggests that principals have a crucial role in improving student achievement by enhancing situations in which teachers work, namely, organisational and family paths. It suggests that principals' leadership practices still matter for teacher professional community and parental involvement in non-western countries. Implications for policy, practice and further research are discussed.
Keywords: Learning-Centred Leadership; Student Achievement; Teacher Professional Community; Parental Involvement